If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1Ln(2 + X) = 6 8 + (2 * -1nL + X * -1nL) = 6 8 + (-2nL + -1nLX) = 6 Solving 8 + -2nL + -1nLX = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -2nL + -8 + -1nLX = 6 + -8 Reorder the terms: 8 + -8 + -2nL + -1nLX = 6 + -8 Combine like terms: 8 + -8 = 0 0 + -2nL + -1nLX = 6 + -8 -2nL + -1nLX = 6 + -8 Combine like terms: 6 + -8 = -2 -2nL + -1nLX = -2 Reorder the terms: 2 + -2nL + -1nLX = -2 + 2 Combine like terms: -2 + 2 = 0 2 + -2nL + -1nLX = 0 The solution to this equation could not be determined.
| x+x+2=146 | | -1.8=3+33y-33y | | X-5=3-2 | | 3x+x=196 | | 13.4583333333= | | 54n^2-70n+55=0 | | 19x-17x=10 | | x+x+5369=210355 | | x^2+7x-86=0 | | a^4-4b^4= | | 9z-13=11z+27 | | 8x-7x=9 | | (9b-2)-4(2b+3)=4 | | (9b-2)-4(2b+3)-4= | | x+2.5+x=5.5 | | x+(x+2)+11= | | 8i= | | 45(x^4y^10)/(9x^6y^6) | | 2y-4x-92=8-3y-4x | | 6p-(2)-(3p)=16 | | 3/Y-3/7Y=5 | | 7-y-y=(-1) | | x(x+6)-40=0 | | 10x-6+18x-6(2x-4)=2 | | 2(x-3)=5(x-6) | | 4x-23=27 | | 2(2x+1)-3x=-6 | | 1.6/0.9=z/7.9 | | 6-5(2x+1)=11 | | 10x^2-390=0 | | 10x^2-139x-390=0 | | 5-(2x+3)=-25 |